The Off-Label use of antidepressants for the treatment of obesity: a review - Galdencio, Eliseu Marques; Silva, Graziely Pereira da; Dantas, Luciana Arantes (Brazilian Journal of Science, 2022)
Obesity is a chronic disease characterized by excessive accumulation of fat in the body. In order to consider a person as obese his body mass index must be equal to or greater than 30 kg m². In Brazil, more than 20 million people are obese. Considering adult population, 12.5% of them are men and 16.9%, women. About 50% are overweight. Currently, there are not many drug options available for the treatment of obesity. Faced with this reality, the Off-Label use of medications emerged as an alternative, being carried out individually for each patient. Among these Off-Label drugs are antidepressants. The study aims to describe and analyze the most prescribed Off-Label antidepressants for the treatment of obesity. It is important to emphasize that the psychiatric evaluation, before each prescription and administration of the drug, should under the guidelines approved by responsible organs. For these reasons, identifying the risks and inappropriate use of these drugs, with Off-Label use for obesity, should actively encourage future research that promotes preclinical and clinical trials on this pathology.